An Alternative Model of Care for the Treatment of Adolescent Athletes with Extension-Based Low Back Pain: A Pilot Study. - Mitchell Selhorst; Richard Rodenberg; Nick Padgett; Anastasia Fischer; Reno Ravindran; James MacDonald (International Journal of Sports Physical Therapy)
# Background and Purpose Half of adolescent athletes report low back pain (LBP) and there is a significant risk of vertebral injury in this population. The current model of care for adolescent athletes with LBP is to first confirm a medical diagnosis of spondylolysis which frequently requires advanced imaging. However, routine use of advanced imaging increases cost, delays treatment, and can expose the athlete to radiation.